Pediatric allergy and immunology for patients and parents: challenges of developing website and social network during COVID-19 pandemic in Brazil - Marina Mayumi Vendrame Takao; Fabiana Silveira de Souza; Luísa Riccetto; Rosana Evangelista-Poderoso; Adriana Gut Lopes Riccetto; Marcos Tadeu Nolasco da Silva (Sociedade de Pediatria de São Paulo, 2023)
Abstract Objective: To describe the development of a website and the creation of a social network account about pediatric allergy/immunology with reliable information, to promote education and have a channel for patient-doctor contact. Methods: This is a descriptive study. A survey was conducted with 93 patients (12 years and older) and caregivers of a Pediatric Allergy/Immunology outpatient clinic, to assess internet usage patterns of potential users. A webpage in Portuguese and an Instagram® account were launched in which it was created an area for patient-doctor communication in the pandemic context. Results: Among 93 participants, 77% were female, 82% caregivers. Median age was 33.2 years, family income 403 dollars/month. The internet was accessed via smartphone by 81,7% of the participants; 76% reported using internet to access health information but 72% did not trust on the information from the internet, and 96% believed that an institutional site could provide meaningful information. From the website release in November 6, 2018 to January 20, 2022, it was counted 10,062 page views by 4,896 users; 55% were 18-34 years old, 70.2% female. Instagram® account gathered 882 followers. Website went through a period of instability during which access were not counted. Due to social isolation during COVID-19 pandemic, the website served as a tool for first response to help patients and doctors. Conclusions: Patients and caregivers of the Pediatric Allergy/Immunology service, consulted about digital tools, considered the information supported by a teaching/research institution timely and relevant. The website and Instagram® account have both performed well and shown good return in relation to hits, and results are continuously being evaluated. During COVID-19 pandemic, the website has been connecting patients/families and doctors.